2019
DOI: 10.1016/j.jddst.2019.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Silodosin oral films: Development, physico-mechanical properties and in vitro dissolution studies in simulated saliva

Abstract: Silodosin oral films: Development, physico-mechanical properties and in vitro dissolution studies in simulated saliva

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…The strength determined by the TS is important for handling and packaging the OF. 60 Visser et al 61 defined as Critical Quality Attributes for orodispersible films TS >2 MPa and E > 10%, thus the OFs produced, regardless of the type of polymer, presented desirable mechanical properties for orodispersible films.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The strength determined by the TS is important for handling and packaging the OF. 60 Visser et al 61 defined as Critical Quality Attributes for orodispersible films TS >2 MPa and E > 10%, thus the OFs produced, regardless of the type of polymer, presented desirable mechanical properties for orodispersible films.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…On the other hand, CMC presented faster release since the maximum release of caffeine (81.1% ± 2.14) occurred after 4 min. Alhayali et al 60 observed, for HPMC-based films with silodosin, for the symptomatic treatment of benign prostatic hyperplasia in men, a release of 80% of the active principle after 10 min.…”
Section: In Vitro Release Profile and Release Kineticsmentioning
confidence: 99%
“…The oral strip technology is formulated for a bedridden and geriatric patient who has difficulty in swallowing. [15] The solvent-casting method was used for preparing an OFDS by the direct casting of OLM NC into a polymeric solution. This oral strips help in improving the bioavailability of OLM.…”
Section: Original Articlementioning
confidence: 99%
“…A modified petri dish method was adopted to evaluate the disintegration time of MD printed and cast ODFs (Alhayali et al, 2019). A watch glass with a 10 cm diameter containing 2 ml PBS pH 7.4 was equilibrated in a shaking incubator (KS 3000 I control, IKA, Germany) set at 60 rpm and 37 ± 0.5 °C.…”
Section: Disintegration Test Of Odfsmentioning
confidence: 99%